Peran Nilai Spiritualitas dalam Pengembangan Desa Wisata Berbasis Masyarakat: Studi Kasus Desa Wisata Silalahi II, Kabupaten Dairi - Lydia De Vega (Lembaga Pengembangan Kinerja Dosen, 2026)
Community-based tourism succeeds only when the values villagers already live by are treated as development assets rather than mere cultural backdrop. This qualitative descriptive study examines the role of spiritual values in the community-based development of Silalahi II Tourism Village, Silahisabungan District, Dairi Regency, a lakeside settlement within the Toba Caldera UNESCO Global Geopark. Data were collected through in-depth interviews with three purposively selected key informants (a tourism village manager, a community elder, and a local homestay entrepreneur), participatory observation, and documentation study, then analyzed using an interactive reduction-display-conclusion model and verified through source and technique triangulation. The findings show that spirituality in Silalahi II is enacted rather than merely professed: it appears as gotong royong (mutual cooperation, locally termed marsiadapari) in preparing customary events and welcoming tourists, gratitude toward Lake Toba as a divine gift to be safeguarded, moral responsibility for cleanliness and village image, reverence for Batak ancestral heritage, and a Christian-inflected hospitality ethic. These values function as social capital that strengthens collective participation, shapes sincere hospitality, and sustains environmental stewardship. The study concludes that spirituality operates as an unseen moral infrastructure beneath community-based tourism that planners should deliberately integrate, alongside continued capacity building in destination management and digital marketing, to secure the long-term sustainability of Silalahi II.